Monitoring of Data Transmission and Changes in Values of Electromagnetic Field in Living Environment - Kohan, Miroslav; Spronglova, Miroslava; Visnovcova, Nadezda; Misek, Jakub; Spanikova, Gabriela; Jakusova, Viera; Jakus, Jan (Communications - Scientific Letters of the University of Zilina, 2020)
A crucial aspect concerning the intelligent transport systems is data transmission between vehicle and central control and information systems. Transportation needs a reliable system of data transfer based on GSM or WiFi networks. However, these networks employ a wide range of different frequencies which can be harmful to the health of drivers. The detrimental effect of electromagnetic radiation can negatively affect the process of transportation. This study determines the intensity of electric field levels (E) of the radiofrequency electromagnetic field (RF EMF) during the data transmission through the 3G, 4G and local WiFi networks, comparing them with the limit values. Conclusions: Our results showed a significantly higher level of the E-field intensity during 4G transmission in all places. The limit values were not exceeded. The lowest E-field values were found in local WiFi network.
Keywords: intelligent transport systems; data transfer; exposure to electromagnetic field; electric intensity; mobile phone; transmission networks